Forest structure and recovery in selectively logged forests in Sarawak, Malaysia - Bibian, Diway (Japan Society of Tropical Ecology, 2023)
In Sarawak, Malaysia, logging is conducted with a 25-year harvesting cycle; however, it remains largely unclear if this cycle length is sufficient for forest recovery. This study aims to investigate how the structure of logged forests recovered along the periods after logging. We conducted this study in the Anap-Muput Forest Management Unit (AMFMU), Sarawak. We first established permanent sample plots with different logging history; that is, from 5 years to more than 37 years after the most recent logging. Using the various sample plots, we assessed the stem density, basal area (BA), proportion of dipterocarps, growth and mortality. To compare the forest structure of the logged over forests with that of primary forests, we used our previous data of a primary forest in Batang Ai National Park. We found significant differences in the stem density, total BA, and the proportion of dipterocarp among the plots. Generally, the stem density and total BA increased with the period after logging and decreased with diameter at breast height (DBH) size classes, except of tree of ≥60 cm DBH in several plots. The growth rates and mortalities were higher in more recent logged forests. These results indicated that logged forest was recovering with periods after logging partly because of higher growth rate; however, even in a forest of 37 years after logging, the forest structure was not fully recovered compared to the primary forest. Thus, we concluded that a 25-year harvesting cycle in the selective logging system would not be sufficient for the AMFMU forest to recover. We further need other effective strategies with systematic monitoring.